Fuzzy properties in fuzzy convergence spaces - Gunther Jäger (International Journal of Mathematics and Mathematical Sciences)
Based on the concept of limit of prefilters and residual implication, several notions in fuzzy topology are fuzzyfied in the sense that, for each notion, the degree to which it is fulfilled is considered. We establish therefore theories of degrees of compactness and relative compactness, of closedness, and of continuity. The resulting theory generalizes the corresponding crisp theory in the realm of fuzzy convergence spaces and fuzzy topology.